Arabidopsis thaliana thylakoid lumen 18.3 protein (TLP 18.3) gene regulate developmental process - Lin2, Mohammad Israil Ansari1; Tsan-Piao (Current Botany, 2011)
<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Arabidopsis thaliana<span style="font-size: 8pt; font-family: Byington; mso-fareast-font-family: ’Times New Roman’; mso-bidi-font-family: ’Times New Roman’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> thylakoid lumen 18.3 kDa protein (TLP18.3) gene (At1g54780) has a domain of unknown function, which is a family of uncharacterized protein. To examine the developmental regulation of this gene, Arabidopsis thaliana TLP18.3 T-DNA insertion mutant (SALK_109618) and wild type plant were observed for the effect of ABA, NaCl and mannitol on the germination of seeds.Ã‚Â 50 mM NaCl inhibit more germination rate in mutant plants than wild type plants followed by 0.1 Ã‚ÂµM ABA and 20 mM mannitol. But in control condition also mutant plants have less (54%) germination rate than the wild type plant which having germination (77%). Arabidopsis thaliana TLP18.3 T-DNA insertion mutant plants (SALK_109618)Ã‚Â have shown 6-9 days of flowering delay but afterÃ‚Â Agrobacterium mediated transformation of Arabidopsis thaliana TLP18.3 T-DNA insertion mutant with pPZP200GB-TLP18.3 construct rescued the flowering delay and germination. The translational analysis have shown that the TLP18.3 protein accumulation wild type plant of Arabidopsis thaliana and it was not detected in western blot analysis of Arabidopsis thaliana TLP18.3 T-DNA insertion mutant demonstrated that this protein was absent in mutant plants. For the subcellular localization of Arabidopsis thaliana TLP18.3, the protoplast of transformed Arabidopsis thaliana TLP18.3 T-DNA insertion mutant after Agrobacterium mediated transformation with pPZP200GB-TLP18.3 construct which is having GFP green fluorescence image, which was completely overlapped with red autoflorescence of chloroplast image clearly showed the chloroplast localization of TLP18.3.